Group Cohesiveness and Social Loafing in Students: Kohesivitas Kelompok dan Kemalasan Sosial pada Mahasiswa - Ningtyas, Novia Lukita; Maryam, Effy Wardati (Indonesian Journal of Innovation Studies, 2023)
This research was conducted because of the phenomenon where students of Muhammadiyah University of Sidoarjo experience social loafing with individual characteristics feeling worried or feeling that their contribution is not accepted by the group.The purpose of this research is to understand the cohesive realtionship of social loafing for Muhammidiyah University Students Sidoarjo. This research type is correlational quantitative, sampling a population of 10.730 college students. The sample surveyed 336 college students utilizing sampling proportional technique. This data collection technique uses cohesivity scale & social loafing scale. The scale cohesivity validity result shows 18 out of 24 item are valid andsocial loafing scale test result shows 20 out of 24 items are valid. The reliability of the cohesive scale is 0,880 and social loafing scale is 0,903. The data analysis result utilize correlation product moment pearson, indicating r=-0,829, p= 0,000 <0,05 which implies the hypothesis is valid. The higher the cohesivity the lower socail loafing, conversely the lower the cohesivity the lower the social loafing. The contribution of effective cohesiity towards socail loafing is 68,8 %.